Author Correction: Host-associated niche metabolism controls enteric infection through fine-tuning the regulation of type 3 secretion - James P. R. Connolly (Nature Portfolio, 2018)
The original version of this Article contained an error in the spelling of the author David Ruano-Gallego, which was incorrectly given as David R. Gallego. This has now been corrected in both the PDF and HTML versions of the Article.